1965
DOI: 10.1128/aem.13.2.232-235.1965
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Live Tularemia Vaccine Prepared in a Chemically Defined Medium

Abstract: CHAMBERLAIN, ROBERT E. (The National Drug Co., Swiftwater, Pa.). Evaluation of live tularemia vaccine prepared in a chemically defined medium. Appl. Microbiol. 13:232-235. 1965.-A chemically defined medium was prepared which adequately supported growth of a vaccine strain of Pasteurella tularensis. This medium differed from those previously described in: (i) concentration of components, (ii) a requirement for calcium pantothenate to obtain increased growth, and (iii) a low initial pH. Varying the concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
113
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(114 citation statements)
references
References 5 publications
0
113
0
1
Order By: Relevance
“…Bacterial strains were grown overnight from frozen stocks at 37°C in chemically defined PN or Chamberlain's media. Cultures were then diluted 1:100 in 20 ml fresh PN/Chamberlain's media (Chamberlain, 1965) and allowed to grow to a cell density of~1.0 ¥ 10 9 cfu ml -1 . Cultures were centrifuged, washed and resuspended in 1 ml of PBS.…”
Section: High-performance Liquid Chromatography (Hplc) Analysis Of Pomentioning
confidence: 99%
“…Bacterial strains were grown overnight from frozen stocks at 37°C in chemically defined PN or Chamberlain's media. Cultures were then diluted 1:100 in 20 ml fresh PN/Chamberlain's media (Chamberlain, 1965) and allowed to grow to a cell density of~1.0 ¥ 10 9 cfu ml -1 . Cultures were centrifuged, washed and resuspended in 1 ml of PBS.…”
Section: High-performance Liquid Chromatography (Hplc) Analysis Of Pomentioning
confidence: 99%
“…The Francisella, Escherichia coli and Pseudomonas strains used in this study are listed in Table 2. F. tularensis strains were grown on modified Thayer-Martin agar plates (Sandström et al, 1984) at 37°C in 5% CO 2 atmosphere or in Chamberlain medium (Chamberlain, 1965). E. coli and P. aeruginosa strains were grown on blood agar base (BAB; Merck) plates, on minimal medium plates (Vogel and Bonner, 1956) or in Luria-Bertani broth (LB).…”
Section: Bacterial Strains Plasmids Mammalian Cells and Growth Condmentioning
confidence: 99%
“…DNA was introduced into F. novicida U112 and mutant strains exclusively by chemical transformation as described previously (Anthony et al, 1991), with the following modification. Efficient chemical transformation of F. novicida normally requires the use of a complex synthetic medium, Chamberlain's broth (Chamberlain, 1965). In this work it was found that the simple addition of 0.4% glucose rendered fresh TSB equally suitable as a transformation medium.…”
Section: Transformation and Conjugationmentioning
confidence: 93%